James and the giant peach : a children's story - Dahl, Roald; Burkert, Nancy Ekholm (New York : Puffin, 1988)
Wonderful adventures abound after James escapes from his fearful aunts by rolling away inside a giant peach.
870
Keywords: Aunts -- Juvenile fiction; Fairy tales; Fantasy fiction